Esthetical heteronomy as creation principle of a fictional narrative: on the esthetical function of intertextuality: Эстетическая гетерономия как принцип построения художественного нарратива: к эстетической функции интертекстуальности - Kotin, Michaił L. (Przegląd Wschodnioeuropejski, 2021)
The relations between the “main” narrative parts of a belletristic text and its (cross)references to other works of literature and/or music, painting etc. play an important part in the structure and functioning of a literary work. The phenomenon of intertextuality belongs at present to the favourite subjects of the research of texts, among others, of fictional texts. However, some relevant functions of implementation of external esthetical works, both literary texts and other art forms, into a fictional narration have not been investigated yet. This paper presents an analyses of two works of narrative fiction written by Tolstoy and T. Mann, with a special attention to the esthetical function of intertextuality by implementation of cross-references to the works of the composer Beethoven (in the case of Th. Mann also of the poet Goethe). The claim is that intertextuality in the esthetical sphere induces a double esthetical function and determines the phenomenon which I will call “esthetical heteronomy”. Its main feature is a very specific influence of external esthetical sources on the internal esthetical values of the primary text.